Confinement‐Enhanced Selective Oxidation of Lignin Derivatives to Formic Acid Over Fe‐Cu/ZSM‐5 Catalysts Under Mild Conditions. Issue 12 (13th May 2022) - Zhang, Zhaoxia; Han, Peijie; Li, Leisu; Zhang, Xindi; Cheng, Xiaojie; Lin, Jingdong; Wan, Shaolong; Xiong, Haifeng; Wang, Yong; Wang, Shuai
Abstract: Aqueous‐phase oxidation by H2 O2, known as the Fenton‐type process, provides an attractive route to convert recalcitrant lignin derivatives to valuable chemicals under mild conditions. The development of this technology is, however, limited by the uncontrolled selectivity, resulting from the highly reactive nature of H2 O2 and the thermodynamically favored deep oxidation to form CO2 . This study demonstrated that formic acid could be produced with a high selectivity (up to 80.3 % at 313 K) from the Fenton‐type oxidation of guaiacol and several other lignin derivatives over a bimetallic Fe−Cu catalyst supported on a ZSM‐5 zeolite. Combined experimental and theoretical investigations unveiled that the micropores of the zeolite support, which contained active metal sites, preferred to adsorb C2 −C4 intermediates over formic acid because of its stronger dispersive interaction with the larger guest molecules. This confinement effect significantly suppressed the secondary oxidation of formic acid, accounting for the uniquely high formic acid selectivity over Fe−Cu/ZSM‐5. Abstract : Confinement effect : A highly selective production of formic acid from Fenton‐type oxidation of guaiacol, a typical lignin derivative, is achieved on a zeolite‐supported bimetallic Fe−Cu catalyst. The micropores of the zeolite support enable a subtle confinement effect that significantly suppresses the secondary oxidation of formic acid and accounts for the high selectivity.